Simultaneous measurements of adenosine deaminase activity and tuberculostearic acid in pleural effusions for the diagnosis of tuberculous pleuritis. - Muranishi H; Nakashima M; Hirano H; Saitoh T; Takahashi H; Tanaka K; Miyazaki M; Yagawa K; Shigematsu N (Internal medicine (Tokyo, Japan), 1992)
Adenosine deaminase (ADA) activity and tuberculostearic acid (TSA) levels in pleural effusions were measured in 18 patients with active tuberculous pleuritis, 16 patients suspected of having tuberculous pleuritis, 14 patients with carcinomatous pleuritis, and 19 patients suffering from pleuritis of non-malignant and non-tuberculous etiology. In the patients with active tuberculous pleuritis, ADA was elevated in 56% and TSA was positive in 78%. In 83% of these patients, either ADA was elevated or TSA was positive. ADA was elevated together with a positive TSA in 50%. In contrast, TSA was positive in only 6% and ADA was elevated in 24% of the patients with non-tuberculous pleuritis, and none of these patients showed the combination of an elevation of ADA and a positive TSA. These results suggest that simultaneous measurements of both ADA and TSA in pleural effusions are useful for the diagnosis of tuberculous pleuritis.